Pupil decision-making about socio-scientific issues within the science curriculum - Ratcliffe, Mary (International journal of science education, 1997)
This study explores the skills, knowledge and values used by 15-year-old pupils, in a UK school, in making decisions about science-related societal issues. The complexities of the decision-making process, group social interactions, and the interrelationship between affective and cognitive criteria in reasoning, are acknowledged. Boys, undertaking a GCSE science course in which decision-making tasks were an integral feature, were audio-taped during discussion, interviewed, and had their written work analysed. Key features of well reasoned pupil decision-making included: understanding procedures for rational analysis of the problem; awareness and use of available information; clarification of the concerns and values raised by the issue; recognition of how scientific evidence may assist in the decision; motivation to engage fully in discussing the issue; consideration of and respect for differing viewpoints about the issue. (Autorenreferat).